Photo emission characteristics of CNT based light emitting diode - Alim, Jinnah Barkatul; Islam, Tasauf (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.